The paradox of resource-richness: unraveling the effects on financial markets in natural resource abundant economies - Muhammad Imran; Muhammad Kamran Khan; Salman Wahab; Bilal Ahmed; Zhang Jijian (Financial Innovation)
Abstract In the contemporary global landscape, understanding the nexus between financial inclusion and natural resource abundance is crucial, especially for resource-rich nations. This study uses diagnostic tests and method of moments quantile regression to examines this interplay across Australia, Brazil, Canada, China, India, Russia, and the United States. We find that achieving financial inclusion is significantly challenging for countries that heavily rely on natural resources. Diversified income sources and equitable wealth distribution are essential to mitigate these challenges. Additionally, we identify a positive correlation between economic development and financial inclusion, highlighting the mutually reinforcing relationship between growth and inclusivity. Our research also reveals a notable link between adopting renewable energy and improving financial inclusion, suggesting that environmental responsibility and financial accessibility are intertwined. Foreign direct investment has nuanced impacts on financial inclusion, adding depth to our understanding. Overall, stable income from natural resources and diversified economic development emerge as key promoters of financial inclusion. These insights advocate for regionally specific policies and lay a solid foundation for future research and informed policymaking that address financial inclusion challenges and advance sustainable development. Graphical abstract